2016
DOI: 10.1371/journal.pone.0150367
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Acupuncture in Post-Operative Pain Management: A Systematic Review and Meta-Analysis

Abstract: BackgroundPostoperative pain resulting from surgical trauma is a significant challenge for healthcare providers. Opioid analgesics are commonly used to treat postoperative pain; however, these drugs are associated with a number of undesirable side effects.ObjectiveThis systematic review and meta-analysis evaluated the effectiveness of acupuncture and acupuncture-related techniques in treating postoperative pain.Data SourceMEDLINE, Cochrane Library, and EMBASE databases were searched until Sep 30, 2014.Study El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
138
2
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(154 citation statements)
references
References 29 publications
2
138
2
12
Order By: Relevance
“…Acupuncture is an important therapy used in complementary and alternative medicine, and may exert anti-inflammatory effects (11). Acupuncture targets specific acupoints to improve the body microenvironment and thus effectively treat certain diseases (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture is an important therapy used in complementary and alternative medicine, and may exert anti-inflammatory effects (11). Acupuncture targets specific acupoints to improve the body microenvironment and thus effectively treat certain diseases (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Although pain level was not assessed in most of the papers cited in this review, acupuncture is known to reduce postoperative pain [96], which is a risk factor of POCD [97]. As indicated in the systematic view conducted by Wu and colleagues in 2016 [98], acupuncture was 16 Oxidative Medicine and Cellular Longevity associated with less postoperative pain one day after surgery than control treatment, although it could not reduce the use of opioid analgesic in patients. Pain research on animals showed that acupuncture could suppress inflammation and reduce the levels of reactive oxidative species.…”
Section: Reducing the Use Of Anesthetic Agents Promoting Patientmentioning
confidence: 91%
“…Acupuncture, a noninvasive and nonpharmacological adjunctive intervention, has been widely applied for sedative and analgesic purposes . In addition to the conventional manual acupuncture, electrical acupuncture and transcutaneous electrical acupoint stimulation (TEAS) have also been employed in clinical practice.…”
Section: Introductionmentioning
confidence: 99%